Evaluasi dan Penyesuaian Sistem Ventilasi Pada Tambang Batubara Bawah Tanah Lubang 02 PT.Cahaya Bumi Perdana, Kota Sawahlunto, Provinsi Sumatera Barat. - Rizki Putri Bungo; Bambang Heriyadi (Departemen Teknik Pertambangan FT UNP, 2020)
Abstract.PT.Cahaya Bumi Perdana is one of the underground coal mining companies in Sawahlunto City that applies the room and pillar mining method. The ventilation system used is a forcing system by arranging the blower in a relay. The blower system installation is not followed by the suction blower installation, so that dirty air is not immediately circulated out. Dirty air resulting from mining activities from one front is pumped back to the next front and increases the increase in dust density and temperature. From the results of temperature measurements in the main 02 hole (L02U) 28.6ºc and in the accompaniment 02 hole (L02P) 26.9ºc. The average humidity in L02U is 91.4% and in L02P 90.3%. This is contrary to government regulations in Kepmen 1827 K / 30 / MEM / 2018 which states